2016
DOI: 10.3982/ecta13447
|View full text |Cite
|
Sign up to set email alerts
|

No-Bubble Condition: Model-Free Tests in Housing Markets

Abstract: We test for the existence of housing bubbles associated with a failure of the transversality condition that requires the present value of payments occurring infinitely far in the future to be zero. The most prominent such bubble is the classic rational bubble. We study housing markets in the United Kingdom and Singapore, where residential property ownership takes the form of either leaseholds or freeholds. Leaseholds are finite‐maturity, pre‐paid, and tradeable ownership contracts with maturities often exceedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(17 citation statements)
references
References 97 publications
(132 reference statements)
1
16
0
Order By: Relevance
“…Recent empirical evidence for housing market bubbles in various countries includes: Gomez-Gonzalez et al (2018); Vogiazas and Alexiou (2017) and Engsted et al (2016) for OECD countries; Shi (2017) for certain regional markets in the US; Dermani et al (2016) for Sweden; Shi et al (2016) for Australia; Shi and Kabir (2018) for New Zealand; Kim and Lim (2016) for Korea; Glaeser et al (2017) for China; Huang and Shen (2017) for Hong Kong; Boelhouwer (2017) for Netherlands; and, Yip et al (2017) for Malaysia. In contrast, Giglio et al (2016) found no evidence of the violation of the transversality condition in the UK and Singapore housing markets indicating no support for the presence of a bubble. mortgage financing vehicles, e.g., Wilmarth (2009), to create the housing market bubble that subsequently collapsed in 2008-2009. Prior to the housing market failure, criticism of the US mortgage system was muted and claims for innovation and superiority over mortgage financing methods used in other countries were common.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Recent empirical evidence for housing market bubbles in various countries includes: Gomez-Gonzalez et al (2018); Vogiazas and Alexiou (2017) and Engsted et al (2016) for OECD countries; Shi (2017) for certain regional markets in the US; Dermani et al (2016) for Sweden; Shi et al (2016) for Australia; Shi and Kabir (2018) for New Zealand; Kim and Lim (2016) for Korea; Glaeser et al (2017) for China; Huang and Shen (2017) for Hong Kong; Boelhouwer (2017) for Netherlands; and, Yip et al (2017) for Malaysia. In contrast, Giglio et al (2016) found no evidence of the violation of the transversality condition in the UK and Singapore housing markets indicating no support for the presence of a bubble. mortgage financing vehicles, e.g., Wilmarth (2009), to create the housing market bubble that subsequently collapsed in 2008-2009. Prior to the housing market failure, criticism of the US mortgage system was muted and claims for innovation and superiority over mortgage financing methods used in other countries were common.…”
Section: Introductionmentioning
confidence: 80%
“…Difficulties of pricing and trading securities with cash flows impacted by US mortgage contract design features combined in a perverse fashion with originate-to-distribute underwriting procedures used in the creation of collateralised mortgage obligations and related 1 In addition to theoretical studies on the definition and measurement of >housing market bubbles=, there is rapidly accumulating evidence on bubbles emerging in various countries. Included in studies on defining and measuring bubbles are: Shi (2017); Bono et al (2017); Giglio et al (2016); Phillips et al (2015) and Himmelberg et al (2005). Recent empirical evidence for housing market bubbles in various countries includes: Gomez-Gonzalez et al (2018); Vogiazas and Alexiou (2017) and Engsted et al (2016) for OECD countries; Shi (2017) for certain regional markets in the US; Dermani et al (2016) for Sweden; Shi et al (2016) for Australia; Shi and Kabir (2018) for New Zealand; Kim and Lim (2016) for Korea; Glaeser et al (2017) for China; Huang and Shen (2017) for Hong Kong; Boelhouwer (2017) for Netherlands; and, Yip et al (2017) for Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Following the Lai and Van Order (2010, 2017) framework, we define the "fundamental" value as the price given an information set, Ω where the transversality condition means that the second term approaches zero holds (Giglio et al 2016). This gives the equilibrium condition for holding property at time t as follows:…”
Section: Basic Modelling Of House Price Growthmentioning
confidence: 99%
“…One of the most developed and used types of models in the last decade is the Macro Asset Pricing (MAP) model, based on the macroeconomic theory of growth and consumption as a measure to quantify the value of financial assets. Among them, the habit formation models, long‐term risks, rare disasters, limited participation, those based on intermediaries and those of learning stand out (Barro & Jin, 2021; Beeler & Campbell, 2012; Giglio et al, 2016; Zhiguo He & Krishnamurthy, 2018; Kleibergen & Zhan, 2020). In the case of habit models, the influence of consumer habits on the price of assets is described.…”
Section: Introductionmentioning
confidence: 99%